Penafsiran Ayat-Ayat Thaharah (Wudhu, Mandi Junub, Tayamum, Dan Konsep Kesucian Dalam Al-Qur’an) - Fauzan Murtadho; Edi Hermanto (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
This study examines the interpretation of verses on thaharah (purification) in the Qur’an using a thematic interpretation approach (tafsir maudhu’i). The focus of the study is on verses related to purification practices such as ablution (wudhu), ritual bathing (ghusl), dry ablution (tayammum), and the physical and spiritual dimensions of purity, particularly in Qur’an Surah Al-Baqarah verse 222, Al-Ma’idah verse 6, and At-Taubah verse 108. This research aims to understand the normative and contextual meanings of purification verses and their relevance to Muslim life. The method employed is qualitative research with a library research approach, utilizing the Qur’an and classical as well as contemporary Qur’anic commentaries as primary sources. The findings indicate that the concept of thaharah in the Qur’an is not limited to ritual cleanliness but also encompasses spiritual, ethical, and social values that contribute to the formation of individual piety and Islamic social order.